Penyelenggaraan Sunat Massal Gratis sebagai Strategi Kesehatan Preventif di Kelurahan Bontolebang - Musriwan Musriwan; Risdayani Risdayani; Andi Dahmayanti (Universitas Pahlawan Tuanku Tambusai, 2026)
Financial constraints and limited access to healthcare services mean that some children in Bontolebang Village, North Galesong Sub-district, Takalar Regency have not yet undergone circumcision. This community service initiative aims to improve access to preventive healthcare services through free mass circumcision. The implementation involved coordination between students from the STIBA Makassar Islamic Institute’s Community Service Programme (KKN) and the Galesong Utara branch of Wahdah Islamiyah, the selection of participants, and the preparation of medical equipment and healthcare personnel. The target group comprised 16 children from various neighbourhoods in Bontolebang Village. The results of the activity showed that 13 children successfully underwent free circumcision, with a positive response and high enthusiasm from the community. In addition to helping the community access healthcare services, this activity also raised awareness of the importance of circumcision as a means of maintaining health and practising Islamic teachings.